Encouraging Innovativeness in universities through market orientation practices - Jebarajakirthy, C.; Sathana, V. (The University of New South Wales, 2015)
Market oriented organizations are committed to understanding and satisfying customer needs. Market oriented firms innovate, develop and modify their products and services to satisfy their customer expectations and preferences. The main aim of this study is to investigate the influence of market orientation on innovation in universities. The findings of this study are useful to enhance innovativeness of the courses and services provided by universities and other higher education institutions through market orientation practices. The sample comprised 300 managers attached to faculties and schools in Sri Lankan universities. The surveys were administered for data collection. All the three components of market orientation, i.e., Intelligence Generation, Intelligence Dissemination and Responsiveness to Intelligence, significantly and positively influenced Innovation in universities. From these findings, implications for theory and practice have been discussed.